Amphiphilic poly(ethylene glycol)-poly(ε-caprolactone) AB2 miktoarm copolymers for self-assembled nanocarrier systems: synthesis, characterization, and effects of morphology on antitumor activity. Issue 4 (15th December 2014) - Yoon, Kwonhyeok; Kang, Han Chang; Li, Li; Cho, Hana; Park, Mi-Kyoung; Lee, Eunji; Bae, You Han; Huh, Kang Moo
Abstract : Miktoarm-structured PEG-PCL2 copolymers with morphological versatility for drug delivery. Abstract : In this study, a series of amphiphilic AB2 -type 3-miktoarm copolymers consisting of hydrophilic poly(ethylene glycol) (PEG) as the A arm and hydrophobic poly(ε-caprolactone) (PCL) as the two B arms were synthesized through the ring-opening polymerization of ε-caprolactone (CL) using a PEG macroinitiator with a bi-arm structure. The self-assembly behavior, drug-loading capacities, and controlled drug release features of the PEG-PCL2 miktoarm copolymers were compared with those of their linear diblock counterparts (PEG-PCL). The PEG-PCL2 miktoarm copolymer with a relatively short PCL arm length (PEG volume fraction, f PEG = 0.55) self-assembled in aqueous solution to form a spherical micelle structure. However, cylindrical micelles were observed for the miktoarm copolymers with long PCL arms ( f PEG = 0.15–0.32), whereas the corresponding linear counterparts consistently formed spherical micelle structures regardless of the PCL arm lengths. Drug-loading using doxorubicin (DOX) as the model drug indicated that the PEG-PCL2 cylindrical micelles possessed superior drug-loading capacities compared with the spherical micelles of the corresponding diblock copolymers. Furthermore, although the DOX-loaded cylindrical micelles exhibited a slower release rate than the DOX-loaded spherical micelles, the former exhibited higher cellular uptake and improved cytotoxic effects than the latter. These findings demonstrate the useful morphological versatility of the miktoarm-structured PEG-PCL block copolymers in comparison with the conventionally used linear diblock copolymers in the design of self-assembled nanocarriers for efficient drug delivery.